De très grands corpus pour l’étude diachronique du français : annotations, informations métalinguistiques et paratextes - Mathieu Goux (Humanités Numériques)
Corpus linguistics and very large equipped corpora have been used for several decades for the diachronic study of the French language. They have made it possible to refine our knowledge of its evolution, and to bring to light phenomena that had not been studied until then. However, their constitution and their search functionalities suffer from certain blind spots originating in the annotation procedure they used and the way they consider philological, paleographic and paratextual information. This contribution reviews these difficulties and makes several suggestions for the development of procedures of encoding and analysis.